PERANCANGAN SISTEM INFORMASI PENJUALAN TANAH KAVLING BERBASIS WEB PADA KAVLING SOUDARA NGAMPIN-AMBARAWA - Ani Syarifatun Nisa; Priyadi Priyadi; Candra Supriadi (LPPM Politeknik Pratama Kendal, 2026)
Kavling Soudara is a land plot sales business located in Ngampin, Ambarawa. Manual marketing and sales recording processes cause limited marketing reach, data recording errors, and difficulties in sales management and reporting. This study aims to design and develop a Web-Based Land Plot Sales Information System to support marketing activities, customer data management, and sales reporting. The research method used is the Waterfall system development method, which includes requirements analysis, system design, implementation, and testing. The result show that the developed system is able to improve operational efficiency, reduce data management errors, and provides faster and more accurate sales information.